Multivariable frequency response methods for colored-noise optimal Kalman filter - ARCASOY, CC (Amer Automatic Control Council, 1995)
[Abstract Not Available]
1995 American Control Conference -- JUN 21-23, 1995 -- SEATTLE, WA